The Influence of Steel Fiber on the Characteristics of Paving Blocks - Ekapraja, Huda; Mudiyono, Rachmat (Universitas Islam Sultan Agung, 2025)
This study aims to (1) evaluate the effect of steel fibers on the characteristics of paving blocks and (2) determine the optimal mixture composition of steel fibers, cement, sand, and water. The composition variations of cement, steel fibers, and sand were 0%:30%:70%, 1%:30%:69%, 2%:30%:68%, and 2.5%:30%:67.5%, with a constant water-cement ratio (W/C) of 0.5. The characterization involved physical properties (density and water absorption) and mechanical properties (compressive and flexural strength). The results showed that water absorption and compressive strength for Sample A were 8.37% and 17.515 MPa, Sample B: 8.47% and 25.306 MPa, Sample C: 9.22% and 22.227 MPa, and Sample D: 9.92% and 23.388 MPa. Based on the SNI 03-0691-1996 standard, only Sample B met the quality requirement for grade B. The optimal composition for producing paving blocks with superior characteristics was 1%:30%:69% (Sample B), which achieved the lowest water absorption (8.47%) and the highest compressive strength (25.306 MPa). This result suggests that incorporating 1% steel fiber enhances paving block quality by reducing water absorption while improving mechanical strength.